Question

Solve the given initial-value problem.

y''' + 3y'' − 13y' − 15y = 0, y(0) = y'(0) = 0, y''(0) = 1

Answer #1

Use the Laplace transform to solve the given initial-value
problem.
y'' − 6y' + 13y = 0, y(0) = 0, y'(0) =
−5
#14 7.3
y(t) ?
please show work and circle the answer

Solve the given initial-value problem.
2y'' + 3y' −
2y = 10x2 −
4x − 15, y(0) = 0,
y'(0) = 0

Solve the initial value problem: y' +3y = 10sint when y(0) =
0

Solve the following initial value problem.
y′′ − 4y′ + 3y = 5x +
ex, y(0)
= 0, y′(0) = 5

Solve the initial value problem
3y'(t)y''(t)=16y(t) , y(0)=1,
y'(0)=2

Solve the initial value problem: 9y′′−18y′+15y=09y″−18y′+15y=0,
y(π/3)=2y(π/3)=2, y′(π/3)=1.y′(π/3)=1.Give your answer as y=...
y=... . Use xx as the independent variable.

Please solve the listed initial value problem:
y'' + 3y' + 2y = 1 - u(t - 10); y(0) = 0, y'(0) = 0

Solve the given initial-value problem.
y''' + 6y'' +
9y' = 0, y(0) = 0,
y'(0) = 1, y''(0) = −6

Solve the given initial-value problem.
y''' + 14y'' + 49y' = 0, y(0) = 0, y'(0) = 1, y''(0) = −5

solve the given initial-value problem
y"-100y=15, y(0)=1, y'(0)=0

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 3 minutes ago

asked 5 minutes ago

asked 6 minutes ago

asked 19 minutes ago

asked 47 minutes ago

asked 50 minutes ago

asked 58 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago